First-time boost beats experience: The effect of past eligibility on turnout. (March 2016) - Bhatti, Yosef; Hansen, Kasper M.; Wass, Hanna
Abstract: Recent findings from the US indicate a clear positive causal effect of past eligibility on voting in subsequent elections. Based on individual-level register data from four elections held in Denmark and Finland, we find that past eligibility either decreases voting propensity or has a zero effect among young voters. The hype associated with the first elections thus appears to cancel out the habit among young adults in countries where the institutional barriers against voting are weak. Moreover, differences across the types of elections can be noted. The negative effect of past eligibility is strongest in elections characterized by low saliency, implying that high-salient elections mobilize all voters equally and therefore narrow the gap between first and second-time eligible voters. Highlights: Findings from the US show a positive causal effect of past eligibility on turnout. We test this using individual-level register-based data from Denmark and Finland. In this context, past eligibility decreases voting propensity or has a zero effect. The negative effect is strongest in elections characterized by low saliency. Differing results might be due to lower barriers against voting in the Nordic countries.